Antibiotics for growing-fattening swine - Richardson, D.; Soule, R.P. Jr.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Duroc Jersey and Poland China littermates of the same sex were used in each trial; however, males were used in trials 1 and 3, and females in trials 2 and 4. The pigs were selected for uniformity as much as possible and allotted at random into three groups. Group 1 was assigned the basal ration; group 2, basal plus 10 mg. of Aureomycin HCl per pound of feed, and group 3, basal plus 10 mg. of Terramycin HCl per pound of feed. Aureomycin HC1 was supplied from Aurofac 2A and Terramycin HC1 from Bi-Con TM5. All pigs in trials 1 and 2 were treated with sodium fluoride to remove worms. Pigs in trials 3 and 4 were not treated. A complete ration was used and,the pigs were individually self-fed. The ration contained 18 percent protein until the pigs reached approximately 75 pounds body weight. It was then lowered to 15 percent protein until the pigs reached 125 pounds body weight. The protein was reduced to 12 percent for the remainder of the feeding period. Table 33 shows the composition of the basal ration. The pigs were slaughtered at approximately 225 pounds for carcass studies.
Keywords: Swine; Antibiotics; Aureomycin; Terramycin HCl